PERAN THRESHOLD DALAM TATA KELOLA KEBIJAKAN DI INDONESIA - Roy Sanjaya; Riezky Aditya Ramadhan; Marco Gregorius Suitela (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2022)
Indonesian regulatory governance today requires Economic Analysis of Law (EAL) through Cost Benefit Analysis (CBA) and Regulatory Impact Assessment (RIA) as a tool to be carried out in the process of formulating, establishing and implementing policies. However, the regulatory governance has not definitively carried out the concept of threshold within the analysis process. This research emphasizes the need to establish the threshold concept so EAL can be executed for policies that have strategic and national impacts to the society.